Extended resections for hilar cholangiocarcinoma - Neuhaus, P; Jonas, S; Bechstein, W O; Lohmann, R; Radke, C; Kling, N; Wex, C; Lobeck, H; Hintze, R (Annals of surgery, 1999)
To evaluate different strategies for extended resections of hilar cholangiocarcinomas on radicality and survival. Surgical resection of hilar cholangiocarcinoma is the only potentially curative treatment. Resection of central bile duct carcinomas, however, cannot always comply with the general principles of surgical oncology to achieve wide tumor-free margins with no-touch techniques. From 1988 to 1998, 95 patients underwent resection of hilar cholangiocarcinoma. Eighty patients had hilar and hepatic resections and 15 had liver transplantation and partial pancreatoduodenectomy (LTPP; i.e., eradication of the entire biliary tract using a no-touch technique). The 60-day death rate was 8%. The overall 1- and 5-year survival rates were 67% and 22%, respectively. Five-year survival rates after R0, R1, and R2 resections were 37%, 9%, and 0%. In a multivariate analysis, surgical radicality was the strongest determinant of survival (p < 0.001). The rate of formally curative resection (R0 resection) was significantly lower in hilar resections (29%) than in liver resections (left hemihepatectomy 59%, right hemihepatectomy 55%, right trisegmentectomy 65%; p < 0.05). The highest rate of R0 resection was observed after LTPP (93%; p < 0.05). Right trisegmentectomies achieved the highest rate of 5-year survival after R0 resection (57%). In a multivariate analysis of patient survival after R0 resection, additional portal vein resection was the only significant factor. The 5-year survival rate after formally curative liver resection with portal vein resection was 65% versus 28% without. Extended resections, especially right trisegmentectomies and LTPP, resulted in the highest rate of R0 resection. Right trisegmentectomy together with portal vein resection best represents the principles of surgical oncology and may be regarded as the surgical procedure of choice. Immunosuppression limits the applicability of LTPP.